Push–pull amino-nitro helicenes: synthesis, (chir)optical properties and self-assembly into thin films. Issue 91 (31st October 2022) - Šámal, Michal; Rybáček, Jiří; Holec, Jan; Hanus, Jan; Vacek, Jaroslav; Buděšínský, Miloš; Bednárová, Lucie; Fiedler, Pavel; Slušná, Michaela Šrámová; Stará, Irena G.; Starý, Ivo
Abstract : A series of regioisomeric push–pull amino-nitro [6]helicenes and a related [7]helicene derivative were prepared and their racemates resolved into enantiomers. Abstract : A series of regioisomeric push–pull amino-nitro [6]helicenes and a related [7]helicene derivative were prepared and their racemates resolved into enantiomers. Compared to the parent helicenes, they exhibit red-shifted UV-Vis spectra, pronounced dipole moments, altered chiroptical properties such as remarkable optical rotatory power, and can form nanocrystalline Langmuir–Blodgett films.